SAT0553 QUANTITATIVE ANALYSIS OF IMAGING FEATURES AT CHEST CT OF PULMONARY ARTERIAL AND VENOUS COMPONENTS IN SYSTEMIC SCLEROSIS-INTERSTITIAL LUNG DISEASE (SSc-ILD). (2nd June 2020) - Bruni, C.; Occhipinti, M.; Camiciottoli, G.; Bartolucci, M.; Pienn, M.; Lepri, G.; Fabbrizzi, A.; Tottoli, A.; Ciardi, G.; Giuggioli, D.; Cuomo, G.; Masini, F.; et al.
Abstract : Background: Interstitial lung disease (ILD) and pulmonary arterial hypertension carry a negative impact on SSc prognosis. Chest CT is the gold standard in assessing ILD and helps in evaluating associated vascular involvement. Objectives: As qualitative analysis of CT scans is limited by low reproducibility and time constraints, we aimed at evaluating parenchymal and vascular features in SSc-ILD by quantitative analysis (QA) of CT scans and testing the relationship with clinical-functional data. Methods: We prospectively enrolled 80 patients who underwent PFTs and chest CT scan spirometry gated at TLC on the same day. Clinical, lung functional and diffusion data, as well as disability indexes were collected. CT images were analyzed by a computational platform for texture analysis of ILD patterns (CALIPER), through Imbio LTA. It quantified the extent of normal pattern (NP %), ground glass opacities (GG %), reticulation (RET %), honeycombing (HC %), total ILD extent (ILD EXT %) and hyperlucent (HL %). Low density areas, representing emphysematous area, were also quantified (LDA %). For lung vessel analysis, a software program developed by the Ludwig Boltzmann Institute for Lung Vascular Research was used. This software determined total, arterial, and venous vascular volumes (TV, AV, VV), and relative volumes (TV%, AV%, VV%), as well as density and number for total, arterial and venous vessels. Results: 43/80 patients/CT scans were eligible for both software analyses, while 36/43 for arterial and venous separation. TV% and total vessel density were correlated positively with mRSS and negatively with %FVC (r=-0.537 and r=-0.382) and %TLC (r=-0.511 and r=-0.648), while vessel tortuosity correlated positively with %DLco. This was confirmed when separately analyzing arterial vessels, while VV% negatively correlated with %FVC, %TLC and %DLco. There was a positive correlation between %ILD patterns and %vascular volumes, being significant for TV%-AV%, total vessels and arterial density. Conversely, %ILD patterns were negatively correlated with VV and number of veins detected, despite positive correlation between VV% and ILD_EXT%. When clustering patients according to %FVC and %DLco with 80% normal cutoff, %FVC allowed clustering according to significantly different ILD patterns extents and vascular features, while %DLCO for vascular features only. Moreover, the consecutive addition of functional impairment and worsening of ILD (from both normal %FVC and %Dlco, to %DLco impairment only to both %FVC and %Dlco impairment), there was a significant increase in %TV, % AV and %VV, with the exception of decrease in %VV and venous density in patients with double impairment versus DLco single impairment. Conclusion: This is the first study showing in SSc a direct correlation between ILD and the increase in lung vascular volume, which is characterized by increase in arterial volume and density and reduction in venous volume and number. These results might be explained by the reduction of pulmonary volume due to fibrosis. However, also a para-physiological mechanism of redistribution of blood flow in lung areas, less involved by ILD, might be considered. Further studies on lung vessel quantification and distribution are ongoing. Disclosure of Interests: Cosimo Bruni Speakers bureau: Actelion, Eli Lilly, Mariaelena Occhipinti Consultant of: Imbio, Gianna Camiciottoli: None declared, Maurizio Bartolucci: None declared, Michael Pienn: None declared, Gemma Lepri: None declared, Alessio Fabbrizzi: None declared, Alessandra Tottoli: None declared, Giuglia Ciardi: None declared, Dilia Giuggioli: None declared, Giovanna CUOMO: None declared, Francesco Masini: None declared, Horst Olschewski: None declared, Federico Lavorini: None declared, Linda Calistri: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim